Hepatitis A and cryptogenic cirrhosis of liver: a case series - Narang, Nisha; Dhanju, Avtar S.; Rikhye, Rishabh; Kaur, Manavdeep; Singh, Adab Alwinder; Jassal, Pankaj (International Journal of Advances in Medicine, 2024)
We are discussing a case series of 12 patients that presented with either compensated or decompensated chronic liver disease that were labelled as cryptogenic cirrhosis of liver after ruling out most of the known causes of chronic liver disease. They were found to be positive for hepatitis A IgG antibody. Cryptogenic cirrhosis has been attributed to various possible causes like non- alcoholic fatty liver disease, various metabolic disorders or occult viral infections. Hepatitis A virus is known to cause acute viral hepatitis. Presence of hepatitis A IgG antibodies in serum of patients with chronic liver disease may act as a clue to fill the voids in our understanding of cryptogenic cirrhosis of liver. Possibility of hepatitis A and various other viruses as potential causes of chronic liver disease needs to be explored.